Diversity and Abundance of Waterbirds in Several Types of Wetlands (Case Study in Sumbernadi Village, South Lampung Regency) - Octavia Widya Maharany; Dian Iswandaru; Sugeng Prayitno Harianto; Gunardi Djoko Winarno (Green Insight Solutions, 2025)
Waterbirds are a group of birds that naturally spend most of their lives in aquatic areas. Sumbernadi Village is located in a coastal area that is part of the wetland ecosystem and includes mangrove, mudflat, fishpond, and ricefield habitats. The aim of this study is to obtain data on the species diversity, species richness, species evenness, species abundance, and species dominance of waterbirds in various wetland types in Sumbernadi Village, South Lampung Regency. The method used for bird data collection was the point count method. In this study, six observation points were established in each wetland habitat (mangrove, mudflat, fishpond, and ricefield), with a distance of 200 meters between each point, and an observation interval of 30 minutes. The results of the study identified 27 species of waterbirds, consisting of a total of 525 individuals from 9 families. These findings indicate that the mud and pond habitats have higher species diversity and richness compared to other habitats, with species diversity (H') values reaching 2.66 and 2.78, respectively. The species richness (R) values in these two habitats are also higher, indicating that environmental conditions in the mud and pond habitats are more supportive for various species of waterbirds to thrive. In contrast, the mangrove habitat shows lower diversity with an H' value of 2.06, indicating that the bird species in this habitat are less varied. On the other hand, the rice field habitat shows good evenness in species distribution with an E value reaching 0.94 and the absence of dominance of certain species (C = 0.11). This indicates a balance in the bird population in the rice field habitat, which can be an indicator of the health of the ecosystem in the area. The results of this study indicate the need for special attention in habitat management and conservation, especially to increase the diversity of waterbirds in less diverse habitats, such as mangroves. These efforts are essential to support healthier and more sustainable ecosystems and ensure that various waterbird species can adapt and survive in changing environments. The ecological index of waterbirds in several wetlands shows that mangroves have relatively low species diversity, while mudflats, ponds and rice fields have higher species diversity.